A Platinum Highly Concave Cube with one Leg on each Vertex as an Advanced Nanocatalyst for Electrocatalytic Applications. Issue 7 (7th April 2015) - Lai, Jianping; Niu, Wenxin; Qi, Wenjing; Zhao, Jianming; Li, Suping; Gao, Wenyue; Luque, Rafael; Xu, Guobao
Abstract The front cover artwork for Issue 07/2015 is provided by a collaboration of groups at State Key Laboratory of Electroanalytical Chemistry, Changchun Institute of Applied Chemistry, Chinese Academy of Sciences, and Departamento de Química Orgánica, Universidad de Córdoba, Spain. The image shows the structure of a Pt highly concave cube with one leg on each vertex and its electrocatalytic applications in electrochemiluminescence and alcohol oxidation. See the Communication itself at http://dx.doi.org/10.1002/cctc.201403042.